Dual-Ligand Functionalized Core-Shell Chitosan-Based Nanocarrier for Hepatocellular Carcinoma-Targeted Drug Delivery - Hefnawy A (Dove Medical Press, 2020)
Amr Hefnawy,1 Islam H Khalil,1,2 Kholoud Arafa,3 Marwan Emara,3 Ibrahim M El-Sherbiny1 1Nanomaterials Lab, Center of Material Science (CMS), Zewail City of Science and Technology, Giza 12578, Egypt; 2Department of Pharmaceutics, College of Pharmacy and Drug Manufacturing, Misr University of Science and Technology (MUST), Giza 12566, Egypt; 3Center for Aging and Associated Diseases, Zewail City of Science and Technology, Giza 12578, EgyptCorrespondence: Ibrahim M El-SherbinyZewail City for Science and Technology, Ahmed Zewail Road, October Gardens, 6th of October City, Giza, EgyptTel +20 238540407Fax +20 238517181Email ielsherbiny@zewailcity.edu.egIntroduction: Hepatocellular carcinoma represents a major health problem with the related death numbers still increasing. Active targeting is considered an attractive choice for the development of selective therapeutics with limited side effects and improved efficiency. In this study, we report the design, development and evaluation of a novel dual-ligand functionalized core-shell chitosan-based nanocarrier for the selective delivery of doxorubicin (DOX) for treatment of hepatocellular carcinoma (HCC).Methods: Following factorial design experiments, DOX was initially complexed with negatively charged carboxymethyl chitosan-g-poly(acrylate) and then the complex was coated with a positively charged dual-ligand (lactobionic acid and glycyrrhetinic acid)-conjugated chitosan. The developed active targeting system was then tested in vitro on Hep-G2 cells using flow cytometry and fluorescence imaging.Results: The obtained results proved the ability of the dual-ligand system to enhance the intracellular uptake of the drug by 4-fold and 8-fold after 4 hrs and 24 hrs of incubation, respectively. The efficiency of the dual-ligand functionalized nanoparticles was also tested in vivo on Wistar rats with induced liver tumors. Testing of serum biomarkers (albumin, creatinine, urea, alpha fetoprotein, ALT, AST and ALP) in addition to histopathological microscopic examination of liver, kidney and heart tissues confirmed the enhanced safety of the developed targeted nanocarrier system compared to the conventional DOX.Discussion: The developed targeted system showed improved intracellular drug delivery and uptake as well as enhanced safety profile. The nanoparticles were formed based on electrostatic interactions providing the flexibility that allows their use as a model for delivery of other drugs and other targets.Keywords: liver cancer, dual targeting, doxorubicin, core-shell nanoparticles